Q. 115.0( 3 Votes )

If f(0) = f(1) =

Answer :



Using the Chain Rule of Differentiation,



= f(ex). ef(x) f(x) + f(ex)ex. ef(x)


At x = 0,



= f(1). ef(0) f’(0) + f’(1). ef(0)


= 0. e0 f’(0) + 2.e0


= 0 + 2.1


= 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If <iMathematics - Exemplar

Differentiate eacMathematics - Exemplar

Differentiate eacMathematics - Exemplar

Differentiate eacMathematics - Exemplar

Differentiate theRD Sharma - Volume 1

Differentiate eacMathematics - Exemplar

Differentiate eacMathematics - Exemplar

Differentiate theRD Sharma - Volume 1

Differentiate theRD Sharma - Volume 1

Differentiate eacMathematics - Exemplar